AtUSP17 negatively regulates salt stress tolerance through modulation of multiple signaling pathways in Arabidopsis. Issue 1 (15th February 2022) - Bhuria, Monika; Goel, Parul; Kumar, Sanjay; Singh, Anil Kumar
Abstract: AtUSP17 is a multiple stress‐inducible gene that encodes a universal stress protein (USP) in Arabidopsis thaliana . In the present study, we functionally characterized AtUSP17 using its knock‐down mutant, Atusp17, and AtUSP17 ‐overexpression lines (WTOE). The overexpression of AtUSP17 in wild‐type and Atusp17 mutant Arabidopsis plants resulted in higher sensitivity to salt stress during seed germination than WT and Atusp17 mutant lines. In addition, the WTOE and FC lines exhibited higher abscisic acid (ABA) sensitivity than Atusp17 mutant during germination. The exogenous application of ethylene precursor 1‐aminocyclopropane‐1‐carboxylic acid (ACC) was able to rescue the salt hypersensitive phenotype of WTOE lines. In contrast, AgNO3, an ethylene action inhibitor, further blocked the effect of ACC during germination. The addition of ACC under salt stress resulted in reduced reactive oxygen species (ROS) accumulation, expression of ABA‐responsive genes, improved proline synthesis, increased expression of positive regulators of ethylene signaling and antioxidant defense genes with enhanced antioxidant enzyme activities. The WTOE lines exhibited salt sensitivity even at the adult plant stage, while Atusp17 mutant exhibited higher salt tolerance with higher chlorophyll, relative water content and lower electrolyte leakage as compared with WT. The BAR interaction viewer database and available literature mining identified AtUSP17‐interacting proteins, which include RGS1, RACK1C and PRN1 involved in G‐protein signaling, which play a crucial role in salt stress responses. Based on the present study and available literature, we proposed a model in which AtUSP17 negatively mediates salt tolerance in Arabidopsis through modulation of ethylene, ABA, ROS, and G‐protein signaling and responses.